Consumers’ Buying Behaviour on Malaysian Traditional Handicrafts - Sin Yee Chan; Yee Wui Lim; Wan Leng Lim (CoMBInES - Conference on Management, Business, Innovation, Education and Social Sciences, 2021)
This paper aims to investigate the factors that influence consumers’ buying behaviour towards Malaysia’s traditional handicraft with the support of the Theory of Planned Behaviour. The variables considered in this study are consumers’ knowledge, subjective norms, perceived behavioural of control and product characteristics. Self-administered online survey questionnaires were distributed and collected from 233 respondents. Consumers’ knowledge, subjective norms and product characteristics have strong direct and positive effect on the purchase intention of Malaysia’s traditional handicraft. However, perceived behavioural of control was found to be not significant. The findings of the current study may assist the organizations and business owners as well as marketers to better understand the Malaysia's traditional handicraft and hopes to devise business strategies to encourage purchases among the local and foreign consumers. The outcome of this study demonstrates the variables that influence Malaysia's traditional handicraft purchase intentions.